RURAL TOURISM AS AN ECONOMIC POTENTIAL FOR PEOPLE IN MALANG RAYA: RURAL TOURISM AS AN ECONOMIC POTENTIAL FOR PEOPLE IN MALANG RAYA - Siti Khusnul Rofiah; Nasikh Nasikh; Grisvia Agustin (International Journal of Economics and Management Research, 2022)
The development of tourist villages is one way to encourage regional economic growth. This research examines the potential of the tourist village of the colorful village of Jodipan, Coban Putri and the tourist village of Pujon which represent tourist attractions in Batu City, Malang City and Malang Regency. The presence of rural tourist destinations brings fresh air to the community. The indicator of the success of the development of this tourism god certainly depends on the mindset of the surrounding community in developing tourism potential with the local wisdom of the village. Of course, the existence of rural tourism in Malang Raya will support regional income and will certainly have a positive impact on increasing national income, reducing poverty and opening new jobs.